Electrical cross-sectional imaging of human motor units in vivo. (April 2022) - Maitland, Stuart; Escobedo-Cousin, Enrique; Schofield, Ian; O'Neill, Anthony; Baker, Stuart; Whittaker, Roger
Highlights: Biocompatible, clinically suitable multi-electrode EMG needle. Hundreds of muscle fibres can be localised from brief (<5 min) recordings. Motor unit territory is shown to overlap in vivo . Abstract: Objectives: In many neuromuscular diseases, weakness results from a disruption in muscle fibres' arrangement within a motor unit. Limitations in current techniques mean that the spatial distribution of fibres in human motor units remains unknown. Methods: A flexible multi-channel electrode was developed and bonded to a clinical electromyography (EMG) needle. Muscle fibre action potentials were localised using a novel deconvolution method. This was tested using simulated data, and in recordings collected from the tibialis anterior muscle of healthy subjects. Results: Simulated data indicated good localisation reliability across all sections of the electrode except the end sections. A corrected fibre density was estimated up to 1.4 fibres/mm 2 . Across five recordings from three individuals, between 4 and 14 motor units were detected. Between 1 and 20 muscle fibres were localised per motor unit within the electrode detection area, with up to 220 muscle fibres localised per recording, with overlapping motor unit territories. Conclusions: We provide the first direct evidence that human motor units spatially overlap, as well as data related to the spatial arrangement of muscle fibres within a motor unit. Significance: As well as providing insights into normal human motor physiology, this technology could lead to faster and more accurate diagnosis in patients with neuromuscular diseases.